Smiles for Life National Oral Health Curriculum: Module 4. Dental Emergencies - Russell Maier; Alan Douglass; Melinda Clark; Mark Deutchman; Joanna Douglass; Wanda Gonsalves; Rocio Quinonez; Hugh Silk; James Tysinger; A. Stevens Wrightson (Association of American Medical Colleges, 2012)
Abstract This resource on acute dental emergencies covers topics for health care providers who take care of ambulatory or hospitalized patients. The module covers a range of topics, including oral pain and infections such as abscesses and cellulitis. In addition, students learn about common trauma to primary and secondary dentition, including the basics of exam, management, and referral. Prevention of injuries is also covered. This resource also covers the Association of American Medical College's basic oral health curriculum competencies for domain 7, emergency care, which apply first-line management to stabilize oral emergencies and traumas to the point of appropriate referral. These competencies include triaging basic dental trauma, managing common dental emergencies to appropriate referral, and developing a diagnostic approach to the patient presenting with oral pain that includes both intraoral and extraoral causes. This resource is designed as an interactive educational tool for both individuals and groups from all aspects of the health care profession. It is a part of the series Smiles for Life: A National Oral Health Curriculum, the nation's most comprehensive and widely used oral health curriculum designed for primary care clinicians. The eight-module course covers the relationship of oral to systemic health, child oral health, adult oral health, dental emergencies, oral health in pregnancy, fluoride varnish, and the oral examination.